Anti-biofilm Action of Chenopodium ambrosioides Extract, Cytotoxic Potential and Effects on Acrylic Denture Surface - Zago, Patrícia Maria Wiziack; dos Santos Castelo Branco, Simeone Júlio; de Albuquerque Bogéa Fecury, Letícia; Carvalho, Letícia Torres; Rocha, Cláudia Quintino; Madeira, Petrus Levid Barros; de Sousa, Eduardo Martins; de Siqueira, Fabiana Suelen Figuerêdo; Paschoal, Marco Aurélio Benini; Diniz, Rafael Soares; Gonçalves, Letícia Machado (Frontiers in Microbiology, 2019)
Considering the challenge to control Candida-associated denture stomatitis, the search for antifungal substances derived from natural sources has become a trend in the literature. In this study the following effects of Chenopodium ambrosioides extract (CAE) were investigated: action against biofilms of Candida albicans, its cytotoxic potential, and changes caused in acrylic resin. The CAE was characterized by High Performance Liquid Chromatography (HPLC). The susceptibility of C. albicans to CAE was investigated by Minimum Inhibitory Concentration and Minimum Fungicidal Concentration (MIC and MFC) tests. Acrylic resin discs were fabricated, and C. albicans biofilms were developed on these for 48 h. Afterwards the discs were immersed for 10 minutes in: PBS (Negative Control); 1% Sodium Hypochlorite (1%SH, Positive Control) or CAE at MIC or 5xMIC. The biofilms were investigated relative to counts and metabolic activity. The cytotoxic potential in keratinocytes and fibroblasts was verified by MTT test. Change in color and roughness of the acrylic resin was analyzed after 28 days of immersion in CAE. The data were analyzed by the ANOVA considering a 5% level of significance. The main compounds detected by HPLC were kaempferol and quercetin. Both MIC and MFC obtained the value of 0.25 mg/mL. The MIC was sufficient to significantly reduce the counts and activity of the biofilm cells (p<0.0001), while 5xMIC resulted in almost complete eradication, similar to 1%SH. Keratinocytes and fibroblasts exposed to the MIC and 5xMIC presented cell viability similar to that of the Control Group (p>0.05). No important changes in acrylic resin color and roughness were detected, even after 28 days. It could be concluded that the immersion of acrylic resin in C. ambrosioides extract in its minimum inhibitory concentration was effective for the reduction of C. albicans biofilms without any evidence of cytotoxic effects or changes in roughness and color of this substrate.